Digital light processing-stereolithography three-dimensional printing of yttria-stabilized zirconia. Issue 7 (May 2020) - Zhang, Jinjin; Wei, Luyang; Meng, Xiuxia; Yu, Fangyong; Yang, Naitao; Liu, Shaomin
Abstract: Digital light processing (DLP)-stereolithography three-dimensional (3D) printing is a well known technique for fabricating components with complex geometries. However, the application of DLP 3D printing to functional ceramics such as 8 mol% yttria-stabilized zirconia (8YSZ), which is one of the most extensively used electrolyte materials for solid oxide fuel cells, is still a great challenge. Therefore, the fabrication of fully 8YSZ monoliths via DLP 3D printing was attempted herein, including the preparation of UV-curable ceramic suspensions, shaping of green bodies, and debinding and sintering. The results show that intact green bodies printed using a 30 vol% 8YSZ-photosensitive resin suspension with 0.1 wt% oleic acid as the dispersant under the optimized printing conditions was sufficiently dense without connected pores after vacuum debinding and sintering in air. The successful fabrication of 8YSZ monoliths with design flexibility via 3D printing provides a simple method for preparing functional ceramic components and may expand the application of 3D printing technology to the energy field.